2014
DOI: 10.5604/20831862.1096047
|View full text |Cite
|
Sign up to set email alerts
|

Bdkrb2 Gene -9/+9 Polymorphism and Swimming Performance

Abstract: The aim of the study was to evaluate the association between swimming performance and the -9/+9 (rs5810761) polymorphism within the BDKRB2 gene in successful competitive swimmers. Best individual swimming results expressed in FINA points achieved at short, middle and long distance events of 157 well-trained Polish swimmers were incorporated into an analysis. Athletes’ genotype and allele distributions were analysed in comparison to 230 unrelated sedentary subjects who served as controls with the χ2 test. All s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 25 publications
3
19
1
1
Order By: Relevance
“…However, Eynon et al [61] found no significant differences in the frequencies of the À9 allele and À9/À9 genotype between 74 Israeli endurance athletes and 240 controls. The same negative results were obtained by Sawczuk et al [62] and Grenda et al [63] in two studies involving 334 endurance athletes from Russia and Poland. Furthermore, Tsianos et al [44] have reported an excess of the TT genotype of the BDKRB2 gene rs1799722 C/T polymorphism in 316 male Mount Olympus marathon runners.…”
Section: Bdkrb2 29 and Rs1799722 T Allelessupporting
confidence: 77%
“…However, Eynon et al [61] found no significant differences in the frequencies of the À9 allele and À9/À9 genotype between 74 Israeli endurance athletes and 240 controls. The same negative results were obtained by Sawczuk et al [62] and Grenda et al [63] in two studies involving 334 endurance athletes from Russia and Poland. Furthermore, Tsianos et al [44] have reported an excess of the TT genotype of the BDKRB2 gene rs1799722 C/T polymorphism in 316 male Mount Olympus marathon runners.…”
Section: Bdkrb2 29 and Rs1799722 T Allelessupporting
confidence: 77%
“…On the other hand, no associations were found between ACE DD and ACTN3 RR + RX genotype combination and jumping and sprint ability in young healthy adults and upper and lower body muscular strength in nonagenarian women ( Bustamante-Ara et al, 2010 ). Further studies analyzing swimming performance and selected gene polymorphisms ( Grenda et al, 2014 ) are need.…”
Section: Discussionmentioning
confidence: 99%
“…Swimming performance is a complex trait that depends on numerous phenotypes, not only muscle contractility, blood oxygen transport capacity, cardiopulmonary function as well as fatty acids and glucose metabolism. It seems that many gene loci, each with a small contribution, rather than single gene polymorphic variants with substantial effects on individual variation of human athletic performance are responsible for swimming performance ( Grenda et al, 2014a , 2014b ). Thus, it is inevitable for sport genetics to focus on analysis of complex interaction of multiple genetic polymorphisms that enhance sport related phenotypes as well as alterations to the genome that do not involve changes in the nucleotide sequences of the genes.…”
Section: Discussionmentioning
confidence: 99%